Alpha heavy chain disease developing in an Asian resident in the United Kingdom and responding to antibiotics. Issue 693 (July 1983) - Ross, I. N.; Thompson, R. A.; Asquith, P.
Abstract : A 40-year-old man born in Bangladesh developed alpha heavy chain disease whilst a resident in the United Kingdom. An incomplete, low molecular weight alpha heavy chain protein, devoid of light chains was demonstrated in his serum. Clinical remission of his disease was achieved by antibiotics alone.